Recontextualização do componente curricular anatomia humana: aprendizagem baseada em problemas no curso de Enfermagem da UFPel - Santos, Mateus Casanova dos (2016)
Between University courses held recent curricular restructuring in order to develop an integrative curriculum, more contextualized and constructive, aimed at the Unified Health System, identifies the course of Nursing. However, as part of this course, the Human Anatomy curriculum component was still being developed according to a traditional pedagogical practice design, featuring, according to Bernstein's theory, a collection curriculum, with an emphasis on a performance model. The thesis aimed at understanding the specific process of re-contextualization of the Human Anatomy curriculum component, through PBL in educational research-action, from a perspective of curriculum integration proposed by the Nursing Course curriculum at UFPel. PBL in the thesis involved a possibility of teaching that is presenting itself as a trend in the basic sciences and in the health formations, including the teaching of Anatomy, is a strategy that aims to converge with the Nursing course UFPel. The method of educational research-action was developed by the research participant interface, characterized as a study of educational case, ethnographic. The study followed between the months of August 2015 and February 2016 the progress of the second semester of the year 2015 the Human Anatomy curricular component of Nursing course at UFPel. In this proposal, in addition to classroom activities and Anatomy Laboratory, it was used as teaching resources, interactive clinical cases of Kurt Kloetzel Plataform, concept maps and three-dimensional teaching platform in Anatomy, constituting a basic tripod Clinical Anatomy problem based on this research, characterized as a form of PBL developed in research. To the extent that developed clinical anatomy-based problems by PBL enabled a way to more regionalized anatomical teaching the human body and the anatomical-clinical approach, contributing to a more inclusive education of health professionals in the application of grounded knowledge in clinical practice of everyday health and particularly the SUS. At the end of formative assessment anatomoclinical evaluation, who toured the learning activities, anatomoclinical density was 69,2%. It was observed that 86,9% (n = 113) of anatomoclinical conceptual maps beheld the regional anatomy, 47,7% (n = 62) systemic anatomy and 61,5% (n = 80) presented the regional and systemic integration in the activity . In the scope of this integration point, there was a detachment of training in collection for an integrative training in clinical anatomy interface. In clinical and regional scope for more development trend of a restricted code, something that before was not done in the traditional teaching human anatomy, which greatly found in only focus of Systemic Anatomy and traditional. The psychic function 'thinking anatomically' was considered a potential reflection when interrelated with the human anatomy to interactive clinical cases of p2K through anatomoclinical conceptual maps, constructing texts and anatomoclinical images of the human body and benefiting a significant learning and training process more active, participatory and inclusive, with the acquirent as the protagonist of your training.